Cognitive Successive Interference Cancellation for Multi-User Visible Light Communication Systems - MARSUKI, AMINAH INDAHSARI; PAMUKTI, BRIAN (Institut Teknologi Nasional, Bandung, 2025)
Wireless communication technology continues to face challenges in meeting high bandwidth demands and the capability to serve numerous users. One promising solution is the non-orthogonal multiple access (NOMA) scheme, particularly through the use of power domain (PD) in the application of visible light communication (VLC) technology. However, PD-NOMA still faces power allocation and detection issues at the receiver end. We propose the Cognitive-SIC-VLC method, which considers the line of sight (LOS). Using combined multiplexing techniques, variations in user positions within the system can result in low SNR (dB) values when detecting a BER threshold of 10-3. In three power allocation experiment scenarios, the third scenario was the best with an initial power allocation of 0.95 and a power increment for each user of 0.05. This has been proven to have very low SNR requirements for users close to the LED.